2013
DOI: 10.1002/zaac.201300261
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of IrHCl2(PPh3)2{P(OEt)3} with Organic Azides: Formation of Aminophosphonium Salts

Abstract: Aminophosphonium salts [Ph3PN(H)R]BPh4 (1) [R = C6H5CH2 (1a), 4‐CH3C6H4CH2 (1b), C6H5 (1c)] were obtained by allowing hydride IrHCl2(PPh3)2{P(OEt)3} to react first with triflic acid and then with the organic azide RN3. The compounds were characterized spectroscopically and by X‐ray crystal structure determination of [Ph3PN(H)CH2C6H4‐4‐CH3]BPh4 (1b). A reaction path for the formation of aminophosphonium cations is also proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…When benzylamine was added to the PPh 3 -I 2 mixture, followed by addition of Et 3 N then benzoic acid (method B), no trace of the corresponding amide could be detected either. Nevertheless, we were able to isolate a major component from this reaction which was identied as (benzylamino)triphenylphosphonium iodide 11 based on spectroscopic analysis. To our delight, it was found that when the amine base was added in the last step (methods C and D), N-benzylbenzamide was obtained quantitatively within 10 min.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When benzylamine was added to the PPh 3 -I 2 mixture, followed by addition of Et 3 N then benzoic acid (method B), no trace of the corresponding amide could be detected either. Nevertheless, we were able to isolate a major component from this reaction which was identied as (benzylamino)triphenylphosphonium iodide 11 based on spectroscopic analysis. To our delight, it was found that when the amine base was added in the last step (methods C and D), N-benzylbenzamide was obtained quantitatively within 10 min.…”
mentioning
confidence: 99%
“…In method B, treatment of the intermediates I with benzylamine led to a rapid formation of solid precipitate. 31 P{H} NMR spectrum of the solution showed an appearance of a 31 P signal at 39.20 ppm (major) as well as two minor peaks at À18.70 and 35.50 ppm (broad) which could be attributed to the presence of aminophosphonium iodide, 11 and possibly a pentavalent phosphorus species IV as well as an iminiumphosphorane V, respectively. 5a,30 Upon addition of Et 3 N, the solids which could be ammonium salts including IV and V became dissolve.…”
mentioning
confidence: 99%